2011
DOI: 10.5530/ax.2011.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant activities of Moringa peregrina Seeds

Abstract: Access Free Rad. Antiox. www.antiox.org of deteriorative changes in the biological systems leading to cell inactivation. [1] Many antioxidant enzymes and compounds present in the cell, mitigate the oxidative stress due to free radicals, by dismutating these free radicals species or by converting these radicals into a less effective forms. [2] Antioxidant supplements or antioxidant-rich food are used to help the human body reduce oxidative damage from free radicals and active oxygen species. [3] Other synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…Our study suggested that 5-FUinduceddamage to the arterial endothelium may be due to generation of free radicals, resulting in lipid peroxidation (Asirvatham and Christina 2012). Phanolic compounds of Moringa peregrina seeds oil increases SOD and CAT activities in animals, hereby improving antioxidant potential (Hussein, 2010 andKoheil et al, 2011). In the present study, administration of benzene and/or 5flurouracil resulted in a significant decrease in blood GSH, SOD and CAT as well as plasma TC, TG, HDL-C and LDL-C with a significant increase in plasma TBARs compared to the normal control group.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Our study suggested that 5-FUinduceddamage to the arterial endothelium may be due to generation of free radicals, resulting in lipid peroxidation (Asirvatham and Christina 2012). Phanolic compounds of Moringa peregrina seeds oil increases SOD and CAT activities in animals, hereby improving antioxidant potential (Hussein, 2010 andKoheil et al, 2011). In the present study, administration of benzene and/or 5flurouracil resulted in a significant decrease in blood GSH, SOD and CAT as well as plasma TC, TG, HDL-C and LDL-C with a significant increase in plasma TBARs compared to the normal control group.…”
Section: Discussionsupporting
confidence: 53%
“…The anti-Leukopenia effect of Moringa peregrina seeds oil was investigated using leucopenia induced rat model, when injected with benzene and/or 5-flurouracil by 2-weeks Aksoy, 1991 andSobrero et al, 1997. In this study, we observed and reported that Moringa peregrina seeds oil can normalize the levels of hematological parameters, which may be due to the presence of antioxidant phytochemicals (Hussein, 2010 andKoheil et al, 2011). Liver is considered to be the main organ of drug detoxifying organ, some lung marker enzyme levels were measured from plasma.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, Moringa is used as medicine for abdominal pain, headache, and skin protection as well as a laxative (Steinitz et al 2009). Recently, it has been shown that Moringa seeds contain potential anti-inflammatory and anti-oxidant factors (Koheil et al 2011).…”
Section: Introductionmentioning
confidence: 99%